DNA Methylation - and Telomere - Based Biological Age Estimation as Markers of Biological Aging in Donors Kidneys - Pavanello, Sofia; Campisi, Manuela; Rigotti, Paolo; Bello, Marianna Di; Nuzzolese, Erica; Neri, Flavia; Furian, Lucrezia (Frontiers in Medicine, 2022)
The biological age of an organ may represent a valuable tool for assessing its quality, especially in the elder. We examined the biological age of the kidneys [right (RK) and left kidney (LK)] and blood leucocytes in the same subject and compared these to assess whether blood mirrors kidney biological aging. Biological age was studied in n=36 donors (median age: 72 years, range: 19-92; male: 42%) by exploring mitotic and non-mitotic pathways, using telomere length (TL) and age-methylation changes (DNAmAge) and its acceleration (AgeAcc). RK and LK DNAmAge are older than blood DNAmAge (RK vs Blood, p=0.0271 and LK vs Blood, p=0.0245) and RK and LK AgeAcc present higher score (this mean the AgeAcc is faster) than that of blood leukocytes (p=0.0271 and p=0.0245) in the same donor. TL of RK and LK are instead longer than that of blood (p=0.0011 and p=0.0098) and the increase in Remuzzi-Karpinski score is strongly correlated with kidney TL attrition (p=0.0046). Finally, blood and kidney TL (p<0.01) and DNAmAge (p<0.001) were correlated. These markers can be evaluated in further studies as a marker of the biological age of donor organ quality and increase the usage of organs from donors of advanced age, therefore, offering potential translational research in kidney transplantation.